Diagnostic Imaging of Thoracolumbar Spine Traumas: A Comprehensive Systematic Review - Sugih Laksono, Bella; Fauzi Yazidah, Iklima (International Medical Journal Corp. Ltd, 2024)
Background: Thoracolumbar (TL) fractures are among the most common spine injuries encountered in emergency trauma care with burst fractures accounting for 10% to 20% of all spinal fractures. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: MRI is more sensitive than other imaging modalities in the diagnosis of soft tissue and spinal cord injuries.